Cortisol mediates cleaner wrasse switch from cooperation to cheating and tactical deception - Soares, Marta C. (2014)
Recent empirical research, mostly done on humans, recognizes that individuals' physiological state affects levels of cooperation. An individual's internal state may affect the payoffs of behavioural alternatives, which in turn could influence the decision to either cooperate or to defect. However, little is known about the physiology underlying condition dependent cooperation. Here, we demonstrate that shifts in cortisol levels affect levels of cooperation in wild cleaner wrasse Labroides dimidiatus. These cleaners cooperate by removing ectoparasites from visiting ‘client’ reef fishes but prefer to eat client mucus, which constitutes cheating. We exogenously administrated one of three different compounds to adults, that is, (a) cortisol, (b) glucocorticoid receptor antagonist mifepristone RU486 or (c) sham(saline), and observed their cleaning behaviour during the following 45 min. The effects of cortisol match an earlier observational study that first described the existence of “cheating” cleaners: such cleaners provide small clients with more tactile stimulation with their pectoral and pelvic fins, a behaviour that attracts larger clients that are then bitten to obtain mucus. Blocking glucocorticoid receptors led to more tactile stimulation to large clients. As energy demands and associated cortisol concentration level shifts affect cleaner wrasse behavioural patterns, cortisol potentially offers a general mechanism for condition dependent cooperation in vertebrates.